Implementing the Mindfulness-Based Interventions; Teaching Assessment Criteria (MBI:TAC) in Mindfulness-Based Teacher Training - GM Griffith; RS Crane; R Baer; E Fernandez; F Giommi; G Herbette; L Koerbel (SAGE Publishing, 2021)
The Mindfulness-Based Interventions: Teaching Assessment Criteria (MBI:TAC) was originally developed as a tool to assess the teaching competence of mindfulness-based program (MBP) teachers. The tool was made freely available and has since been used by mindfulness-based teacher training organisations internationally. During this time the MBI:TAC has evolved in its usage, from an assessment tool to one which informally supports how MBP teachers are trained. In this article, we first examine the rationale for implementing the MBI:TAC in MBP teacher training; second, we offer practical guidance on ways of integrating the tool into teacher training pathways with awareness of its potential and possible pitfalls; and third, we offer guidance on using the tool as a framework for giving effective feedback to trainees on their teaching practice. Implementing the MBI:TAC in teacher training may support the quality and integrity of MBP teacher training, and thus ensure high quality MBP teachers graduating. In turn this may help avoid the 'implementation cliff' - that is, the quality of an intervention delivery is delivered in optimal conditions when it is being researched, and drops in quality when delivered in sub-optimal, 'real world' conditions.